An impressive choledochal cyst and its surgical resection. (2017) - Galván, Nhu Thao Nguyen; Kumm, Kayla; Yoeli, Dor; Witte, Ellen; Kueht, Michael; Cotton, Ronald Timothy; Rana, Abbas; O'Mahony, Christine A.; Goss, John A.
Highlights: Choledochal cysts are congenital biliary tract dilations that may have vague symptoms, making them difficult diagnoses to make. Cyst resection is the standard of care due to the increased risk of cholangiocarcinoma. Efficient diagnosis and referral to an experienced hepatobiliary center is crucial. Abstract: Introduction: Choledochal cysts are rare congenital dilations of the biliary tree that can present with non-specific symptoms such as abdominal pain, jaundice, cholelithiasis and pancreatitis. Although most commonly identified in children, they can be found in the adult population. However, because of the non-specific symptoms, this diagnosis may be difficult to make in the adult. A physician therefore must keep this diagnosis within their differential, as it may arise in an unexpected patient population who may present with a convoluted work up. Case presentation: In this report, we present the case of a 50-year-old African American woman with recurrent cholelithiasis, cholangitis and eventually obstructive jaundice despite undergoing a laparoscopic cholecystectomy six years prior. Her only work up at that point was a right upper quadrant ultrasound revealing gallbladder sludge, which led to her cholecystectomy. It was the persistence of her symptoms—abdominal pain, cholangitis and obstructive jaundice—previously attributed to chronic cholecystitis and choledocholithiasis that warranted further work up. After multiple physician visits, she was referred to our academic center after an ERCP was performed and she was found to have a dilation of her common bile duct consistent with a choledochal cyst. Furthermore, the ERCP identified multiple bile duct stones within the cyst. This was not identified on her original ultrasound or prior ERCPs. The patient underwent a complete cyst excision with Roux-en-Y hepaticojejunostomy and did well post-operatively. Discussion: This report illustrates how choledochal cysts can be an elusive diagnosis, but may present with repeated infections, recurrent biliary stones, and biliary obstruction despite a cholecystectomy. Had she an MRCP prior to her cholecystectomy, she would likely have avoided multiple surgeries, and years of persistent symptoms. Choledochal cysts are associated with an increased risk of biliary malignancy and therefore cyst excision is the standard of care. Conclusion: Although rare, physicians need to keep this diagnosis in mind, and be aware of the clinical and imaging findings consistent with a choledochal cyst in order to facilitate appropriate work up, referral and treatment.